Factors affecting the development of green tourism based on organic agriculture: A case study of the Northwest region of Vietnam - Hung, Le Van; Nguyen, Nam Danh (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the key factors influencing the development of green tourism based on organic agriculture in Vietnam’s Northwest region. Using a quantitative research design, 362 valid responses were collected and analyzed with SPSS 26 through reliability testing, exploratory factor analysis (EFA), correlation analysis, and linear regression. The findings reveal that seven factors, including tourism resources, tourism development policies, human resources, tourism products, service pricing, facilities and infrastructure, and security and safety, significantly affect the growth of green tourism centered on organic agriculture. The study concludes that improving policy frameworks, enhancing infrastructure, and developing high-quality tourism products are essential to fostering sustainable tourism. The results provide policymakers, local authorities, and tourism enterprises with valuable insights for designing strategies that integrate organic agriculture with eco-friendly tourism, thereby ensuring environmental protection, promoting community participation, and achieving sustainable regional economic development.